Composite optical fiber based on fluorescence detection system and preparation method thereof
Patent Information
- Application Number
- CN202111504218.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-03-26
- Filing Date
- 2021-12-10
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2041-12-10
AI Technical Summary
随着社会的发展以及材料加工技术的进步,传统的石英玻璃光纤已无法满足人们使用中所提出的越来越多的不同要求
将高熔点的金属材料成功复合到柔性高分子聚合物光纤中,形成独特的结构,具有优异的光学性能。柔性高分子聚合物的制备过程中,加入胺菊酯作为反应单体与甲基丙烯酸甲酯聚合,提高了聚合物材料的玻璃化转变温度,产物的热稳定性得到加强;且胺菊酯的存在还可以提高聚合物的均匀性,增强光纤芯层材料的柔韧性;作为光纤芯层材料制备得到复合光纤,可显著降低产品的损耗,改善产品的机械性能,进而提升产品的质量。N-叔丁基-1,1-二甲基-1-(2,3,4,5-四甲基-2,4-环戊二烯-1-基)硅烷胺的加入,能够改善光纤芯层材料的机械性能;且可以降低其吸水率,增强光纤芯层材料的耐水性能;同时在胺菊酯存在的情况下,两者复配使用,使得光纤芯层材料具有更佳的耐水性能、机械性能,且制得的复合光纤的损耗更低,进一步改善产品质量。纤芯棒的材料中加入砷化镓粉和氧化锰,可有效提升复合光纤的光学透过率,同时可进一步降低光纤的损耗。
Smart Images

Figure DEST_PATH_IMAGE002 
Figure DEST_PATH_IMAGE004 
Figure DEST_PATH_IMAGE006
Abstract
Description
Technical Field
[0001] This invention belongs to the field of composite optical fiber technology, specifically relating to composite optical fibers based on fluorescence detection systems and their preparation methods. Background Technology
[0002] Optical fiber is a light transmission tool that utilizes the principle of total internal reflection. The invention of optical fiber has significantly changed human lifestyles. Currently, optical fiber is widely used in fields such as biomedicine, industrial detection, and intelligent manufacturing. Despite its wide range of applications, optical fiber is remarkably simple in terms of its material composition; most optical fibers currently in use are made of silica glass. While some are made from other glasses or polymers, silica glass remains the primary raw material for optical fiber production. With societal development and advancements in materials processing technology, traditional silica glass optical fibers can no longer meet the increasingly diverse requirements of users, such as flexible electronic optical fibers, photoelectric detection optical fibers, biomedical sensing optical fibers, and smart wearable fiber optic fabrics. Therefore, the concept of "multi-material optical fibers" has been proposed, whose components are not limited to a single silica glass but are composed of composite materials with different functions. By integrating materials with different functions, such as optical, electrical, magnetic, and piezoelectric materials, into a single optical fiber or fiber array, the multi-functionality of a single optical fiber is achieved. Composite optical fibers, with their novel, unique, and diverse characteristics, are attracting increasing attention from researchers and have become a hot research direction in the field of optical fiber waveguides. Summary of the Invention
[0003] The purpose of this invention is to provide a composite optical fiber based on a fluorescence detection system and its preparation method. The composite optical fiber has excellent mechanical properties, good heat resistance, and low water absorption. It also has good optical transmittance, low loss, and an expanded range of applications.
[0004] The technical solution adopted by the present invention to achieve the above objectives is as follows: Composite optical fibers based on fluorescence detection systems include: The core rod, whose material components include selenium powder; The fiber core layer is made of fiber optic core material, including pyrethroid-modified polymethyl methacrylate (PMMA). The addition of pyrethroids, acting as a monomer, polymerizes with PMMA, increasing the glass transition temperature of the polymer and enhancing the thermal stability of the product. Furthermore, the presence of pyrethroids improves polymer homogeneity, reduces disordered and crystalline phases, and enhances the flexibility of the fiber core layer. When used as the fiber core layer material to prepare composite optical fibers, it significantly reduces product loss, improves mechanical properties, and thus enhances product quality. The successful composite of high-melting-point metallic materials into flexible polymer optical fibers creates a unique structure with excellent optical performance, significantly reducing loss while maintaining good optical transmittance.
[0005] It should be noted that the preparation methods of optical fiber core materials include: Acephate, methyl methacrylate, initiator, and n-butyl mercaptan are added to the reaction flask of the prepolymerization device in a certain weight ratio. After stirring evenly, the mixture is heated to 80-85°C. The prepolymerized core material is poured into the mold cavity of the rod mold. After reacting at a constant temperature for 40-48 hours, the mixture is heated to 100°C and polymerized for another 10-12 hours to obtain modified polymethyl methacrylate rods.
[0006] It should be noted that the raw material components of the optical fiber core layer material include, by weight, 85-96 parts methyl methacrylate, 4-10 parts pyrethroid, 0-5 parts N-tert-butyl-1,1-dimethyl-1-(2,3,4,5-tetramethyl-2,4-cyclopentadien-1-yl)silaneamine, 0.1-2 parts initiator, and 0.05-3 parts n-butyl mercaptan. The addition of N-tert-butyl-1,1-dimethyl-1-(2,3,4,5-tetramethyl-2,4-cyclopentadien-1-yl)silaneamine improves the mechanical properties of the product; it also enhances rheological dispersion, reduces water absorption, and strengthens the water resistance of the optical fiber core material, thereby reducing the likelihood of contamination. Furthermore, in the presence of pyrethroids, the addition of N-tert-butyl-1,1-dimethyl-1-(2,3,4,5-tetramethyl-2,4-cyclopentadien-1-yl)silaneamine, used in combination, results in better water resistance and mechanical properties of the optical fiber core material, and the resulting composite optical fiber exhibits lower loss, further improving product quality.
[0007] It should be further noted that the core rod material comprises selenium powder, gallium arsenide powder, and manganese oxide; wherein the mass ratio of selenium powder, gallium arsenide powder, and manganese oxide is 1:0.23~0.36:0.08~0.16. The addition of gallium arsenide powder and manganese oxide to the core rod material, followed by heat treatment, allows for the directional crystallization of the semiconductor core, effectively improving the optical transmittance of the composite optical fiber while reducing fiber loss and enhancing the overall performance of the composite optical fiber.
[0008] Another object of the present invention is to provide the use of pyrethroids in enhancing the mechanical and heat resistance properties of optical fiber core materials.
[0009] The above-mentioned method for fabricating composite optical fibers based on fluorescence detection systems includes: The core rod was prepared by melt casting. To prepare the composite optical fiber, a modified polymethyl methacrylate rod is taken and polished according to the required size. Then, a cylindrical hole is machined inside the rod, and a core rod of appropriate size is selected and filled into the modified polymethyl methacrylate rod to obtain a composite preform. Next, it is vacuum solidified at 170~180℃ for 1~1.5h and then drawn on a standard Rasta to obtain the composite optical fiber.
[0010] It should be noted that the fiber drawing temperature in the composite fiber fabrication process is 290~320℃, and the specific drawing speed, feeding speed, drawing temperature and other process parameters depend on the actual drawing situation.
[0011] It should be noted that during the fiber drawing process in the composite optical fiber fabrication steps, the metal electrode material is continuously fed into the preform through pulleys, and then drawn together to form a composite optical fiber; wherein, the aforementioned metal electrode material is one of platinum wire, copper wire, and tungsten wire.
[0012] Another object of the present invention is to provide the use of the above-mentioned composite optical fiber in a fluorescence detection system.
[0013] Compared with the prior art, the present invention has the following beneficial effects: High-melting-point metallic materials were successfully composited into flexible polymer optical fibers, forming a unique structure with excellent optical properties. During the preparation of the flexible polymer, the addition of pyrethroid as a reactive monomer to polymerize with methyl methacrylate increased the glass transition temperature of the polymer material, enhancing the thermal stability of the product. Furthermore, the presence of pyrethroid improved the homogeneity of the polymer and enhanced the flexibility of the fiber core material. As the core material, the resulting composite optical fiber significantly reduced product loss, improved mechanical properties, and thus improved product quality. The addition of N-tert-butyl-1,1-dimethyl-1-(2,3,4,5-tetramethyl-2,4-cyclopentadien-1-yl)silaneamine improved the mechanical properties of the fiber core material and reduced its water absorption rate, enhancing its water resistance. Simultaneously, the combined use of pyrethroid and pyrethroid in the presence of pyrethroid resulted in better water resistance and mechanical properties in the fiber core material, and the resulting composite optical fiber exhibited lower loss, further improving product quality. Adding gallium arsenide powder and manganese oxide to the core rod material can effectively improve the optical transmittance of the composite optical fiber, while further reducing the fiber loss.
[0014] Therefore, the present invention provides a composite optical fiber based on a fluorescence detection system and its preparation method. The composite optical fiber has excellent mechanical properties, good heat resistance, and low water absorption; it also has good optical transmittance, low loss, and an expanded range of applications. Detailed Implementation
[0015] The technical solution of the present invention will be further described in detail below with reference to specific embodiments: The initiator used in the embodiments of the present invention is AIBN.
[0016] Example 1: The raw material composition of an optical fiber core layer material includes, by weight, 92 parts methyl methacrylate, 6 parts permethrin, 1 part initiator, and 1 part n-butyl mercaptan.
[0017] Preparation of an optical fiber core material: Acephate, methyl methacrylate, initiator, and n-butyl mercaptan are added to the reaction flask of the prepolymerization device in a certain ratio, stirred evenly, and heated to 80°C. The prepolymerized core material is poured into the mold cavity of the rod mold and reacted at a constant temperature for 42 hours. Then, it is heated to 100°C and polymerized for another 10 hours to obtain modified polymethyl methacrylate rods.
[0018] Fabrication of a composite optical fiber: The core material is prepared by melt casting. Selenium powder is loaded into a quartz tube with a diameter of 3 mm, heated with a flame gun to turn the powder into a liquid, and then cooled to room temperature. Then, hydrofluoric acid is used to dissolve and remove the glass tube to obtain the core rod. The composite optical fiber was prepared by taking the modified polymethyl methacrylate (PMMA) rod obtained above and polishing it according to the dimensional requirements to obtain a PMMA rod with a diameter of 30 mm and a length of 12 cm. A cylindrical hole with a diameter of 8 mm and a depth of 10 cm was drilled inside the rod using a drilling machine. Then, a fiber core rod with a diameter of 3 mm and a length of 10 cm was selected and filled into the above-mentioned PMMA tube to obtain a composite preform. The preform was then solidified at 180°C for 1 hour in a vacuum drying oven. After solidification, two cylindrical holes with a diameter of 2 mm and a length of 12 cm were drilled on the modified PMMA cladding of the composite preform. The composite preform was then placed on a standard Rasta optics to draw the optical fiber. During the fiber drawing process, metal electrode material was continuously fed into the preform through pulleys, and then drawn together to form the composite optical fiber. The fiber drawing temperature was 300°C.
[0019] Example 2: The raw material composition of an optical fiber core layer material includes, by weight, 90 parts methyl methacrylate, 8 parts permethrin, 0.8 parts initiator, and 1.2 parts n-butyl mercaptan.
[0020] The preparation of the optical fiber core material described above is the same as in Example 1.
[0021] The fabrication of a composite optical fiber is the same as in Example 1.
[0022] Example 3: The raw material composition of an optical fiber core layer material includes, by weight, 88 parts methyl methacrylate, 5 parts permethrin, 0.5 parts initiator, and 0.8 parts n-butyl mercaptan.
[0023] The preparation of the optical fiber core material described above is the same as in Example 1.
[0024] The fabrication of a composite optical fiber is the same as in Example 1.
[0025] Example 4: The raw material composition of an optical fiber core layer material includes, by weight, 92 parts methyl methacrylate, 4 parts N-tert-butyl-1,1-dimethyl-1-(2,3,4,5-tetramethyl-2,4-cyclopentadien-1-yl)silaneamine, 1 part initiator, and 1 part n-butyl mercaptan.
[0026] The preparation of the optical fiber core material described above is the same as in Example 1.
[0027] The fabrication of a composite optical fiber is the same as in Example 1.
[0028] Example 5: The raw material composition of an optical fiber core layer material includes, by weight, 92 parts methyl methacrylate, 6 parts pyrethroid, 4 parts N-tert-butyl-1,1-dimethyl-1-(2,3,4,5-tetramethyl-2,4-cyclopentadien-1-yl)silaneamine, 1 part initiator, and 1 part n-butylthiol.
[0029] The preparation of the optical fiber core material described above is the same as in Example 1.
[0030] The fabrication of a composite optical fiber is the same as in Example 1.
[0031] Example 6: The raw material composition of an optical fiber core layer material includes, by weight, 92 parts methyl methacrylate, 1 part initiator, and 1 part n-butyl mercaptan.
[0032] The preparation of the optical fiber core material described above is the same as in Example 1.
[0033] The fabrication of a composite optical fiber differs from that in Example 1 in that: The core rod is composed of selenium powder, gallium arsenide powder and manganese oxide; wherein the mass ratio of selenium powder, gallium arsenide powder and manganese oxide is 1:0.29:0.11.
[0034] Example 7: The raw material composition of an optical fiber core layer material includes, by weight, 92 parts methyl methacrylate, 6 parts permethrin, 1 part initiator, and 1 part n-butyl mercaptan.
[0035] The preparation of the optical fiber core material described above is the same as in Example 1.
[0036] The fabrication of a composite optical fiber differs from that in Example 1 in that: The core rod is composed of selenium powder, gallium arsenide powder and manganese oxide; wherein the mass ratio of selenium powder, gallium arsenide powder and manganese oxide is 1:0.29:0.11.
[0037] Example 8: The fiber core material is the same as in Example 4.
[0038] The preparation of the optical fiber core material described above is the same as in Example 4.
[0039] The fabrication of a composite optical fiber differs from that in Example 4 in that: The core rod is composed of selenium powder, gallium arsenide powder and manganese oxide; wherein the mass ratio of selenium powder, gallium arsenide powder and manganese oxide is 1:0.29:0.11.
[0040] Example 9: One type of optical fiber core material is the same as that in Example 5.
[0041] The preparation of the optical fiber core material described above is the same as in Example 5.
[0042] The fabrication of a composite optical fiber differs from that in Example 5 in that: The core rod is composed of selenium powder, gallium arsenide powder and manganese oxide; wherein the mass ratio of selenium powder, gallium arsenide powder and manganese oxide is 1:0.29:0.11.
[0043] Comparative Example 1: The raw material composition of an optical fiber core layer material includes, by weight, 92 parts methyl methacrylate, 1 part initiator, and 1 part n-butyl mercaptan.
[0044] The preparation of the optical fiber core material described above is the same as in Example 1.
[0045] The fabrication of a composite optical fiber is the same as in Example 1.
[0046] Experimental Example 1: 1. Determination of refractive index The refractometer was used for measurement.
[0047] A methyl methacrylate solution containing 6% (v / v) of methoxyphenoxyphenate was reacted at 80°C for 42 h, and then further reacted at 100°C for 10 h. The refractive index was measured at 15°C using an Abbe refractometer to be 1.5483 (fiber core material prepared in Example 1). The refractive index of pure polymethyl methacrylate (fiber core material prepared in Comparative Example 1) obtained under the same conditions was measured to be 1.4919. This indicates that methoxyphenoxyphenate and methyl methacrylate successfully underwent a polymerization reaction.
[0048] 2. Thermal Analysis (DSC) Thermal parameters such as glass transition temperature and initial crystallization temperature can be obtained using differential scanning calorimetry (DSC). A Netzsch STA 449C integrated thermal analyzer was used for testing, with an air atmosphere and a heating rate of 10℃ / min, covering a temperature range of 30–200℃.
[0049] The optical fiber core materials prepared in Comparative Example 1 and Examples 1-5 were subjected to the above tests, and the results are shown in Table 1: Table 1. Test results of glass transition temperature sample Glass transition temperature (°C) Comparative Example 1 102.9 Example 1 143.1 Example 2 139.9 Example 3 142.7 Example 4 107.8 Example 5 150.6 Analysis of Table 1 shows that the glass transition temperature of the optical fiber core material prepared in Example 1 is higher than that in Comparative Example 1, indicating that the pyrethroid-modified methyl methacrylate polymer was successfully prepared and used in the preparation of the optical fiber core material. The presence of pyrethroid can effectively increase the glass transition temperature of the core material. The effect of Example 4 is comparable to that of Comparative Example 1, and the effect of Example 5 is comparable to that of Example 1, indicating that the addition of N-tert-butyl-1,1-dimethyl-1-(2,3,4,5-tetramethyl-2,4-cyclopentadien-1-yl)silaneamine has no negative effect on the glass transition temperature of the material, but the glass transition temperature values are different, indicating that N-tert-butyl-1,1-dimethyl-1-(2,3,4,5-tetramethyl-2,4-cyclopentadien-1-yl)silaneamine successfully undergoes polymerization reaction with other components.
[0050] 3. Water absorption rate test Dry the sample in an oven at 60℃ until constant weight, and weigh it; this weight is m1. Then soak it in tap water for 30 minutes, remove it, and weigh it; this weight is m2. The water absorption rate is calculated using the following formula: Water absorption rate % = (m2 - m1) / m1 The optical fiber core materials prepared in Comparative Example 1 and Examples 1-5 were subjected to the above tests, and the results are shown in Table 2: Table 2 Water Absorption Test Results Analysis of Table 2 shows that the water absorption rate of the optical fiber core material prepared in Example 1 was not significantly different from that of Comparative Example 1, while the water absorption rate of the optical fiber core material prepared in Example 4 was significantly lower than that of Comparative Example 1. This indicates that the addition of N-tert-butyl-1,1-dimethyl-1-(2,3,4,5-tetramethyl-2,4-cyclopentadien-1-yl)silaneamine can effectively reduce the water absorption rate of the optical fiber core material and enhance its water resistance. Meanwhile, the effect of Example 5 was significantly better than that of Examples 1 and 4, indicating that the addition of N-tert-butyl-1,1-dimethyl-1-(2,3,4,5-tetramethyl-2,4-cyclopentadien-1-yl)silaneamine in the presence of pyrethroids, and the combined use of the two, resulted in better water resistance of the optical fiber core material.
[0051] Experimental Example 2: 1. Optical performance characterization Optical transmission spectroscopy measurements were performed using a Perkin-Elmer Lambda 900 UV / Vis / NIR spectrophotometer. To test optical transmission loss, a 483nm laser was selected as the light source and coupled into an optical fiber. A photodetector was mounted on a power meter (PD 300-UV, 200~1100nm, OPHIR) to measure the light output intensity. One end of the optical fiber was fixed, and the other end was fixed to a moving stage. Light transmission relative to the radius of curvature was measured by varying the distance between the two ends.
[0052] The composite optical fibers prepared in Comparative Example 1 and Examples 1-9 were subjected to the above tests, and the results are shown in Table 3: Table 3 Optical performance test results Analysis of Table 3 shows that the optical transmittance of the composite optical fibers obtained in Examples 1 and 4 is comparable to that of Comparative Example 1, but their losses are significantly lower. This indicates that using pyrethroids or N-tert-butyl-1,1-dimethyl-1-(2,3,4,5-tetramethyl-2,4-cyclopentadien-1-yl)silaneamine-modified methyl methacrylate polymer to prepare the fiber core material and using it in the preparation of composite optical fibers can effectively reduce the loss of composite optical fibers while maintaining good transmittance. The optical transmittance of the composite optical fiber obtained in Example 5 is comparable to that of Examples 1 and 4, but its losses are significantly lower than those of Examples 1 and 4. This indicates that simultaneously adding pyrethroids and N-tert-butyl-1,1-dimethyl-1-(2,3,4,5-tetramethyl-2,4-cyclopentadien-1-yl)silaneamine-modified methyl methacrylate polymer to prepare the fiber core material and using it in the preparation of composite optical fibers, and combining the two, has a better effect on reducing the loss of composite optical fibers. The optical transmittance of the composite optical fiber prepared in Example 6 is higher than that of Comparative Example 1, and its loss is lower than that of Comparative Example 1. Furthermore, the effect of Example 7 is better than that of Example 1, the effect of Example 8 is better than that of Example 4, and the effect of Example 9 is better than that of Example 5. This indicates that the addition of gallium arsenide powder and manganese oxide to the core rod material has an enhancing effect on both the increase in transmittance and the reduction in loss of the composite optical fiber.
[0053] 2. Mechanical performance testing The tests included bending stiffness and stress, measured using a dynamic mechanical analyzer (DMA, Q800, TA instrument). A 1.5cm fiber was used, and a single cantilever mode was employed. The test frequency range was 0.01–10Hz, the displacement was 50μm, and the temperature was controlled at 37℃. Commercially available silica fiber was used as a control group.
[0054] The composite optical fibers prepared in Comparative Example 1 and Examples 1-9 were subjected to the above tests, and the results are shown in Table 4: Table 4 Mechanical Performance Test Results Analysis of Table 4 shows that the bending stiffness and stress of the composite optical fiber prepared in Example 1 are much lower than those of the control group and lower than those of Comparative Example 1. This indicates that using pyrethroid-modified methyl methacrylate polymer to prepare the fiber core material and using it in the preparation of composite optical fibers can effectively reduce the bending stiffness and internal stress of the composite optical fiber, improve its mechanical properties, and enhance its flexibility. The effect of Example 4 is better than that of Comparative Example 1, and the effect of Example 5 is better than that of Example 1, indicating that the addition of N-tert-butyl-1,1-dimethyl-1-(2,3,4,5-tetramethyl-2,4-cyclopentadien-1-yl)silaneamine has an enhancing effect on improving the mechanical properties of the composite optical fiber. Furthermore, the effect of Example 6 is comparable to that of Comparative Example 1, the effect of Example 7 is comparable to that of Example 1, the effect of Example 8 is comparable to that of Example 4, and the effect of Example 9 is comparable to that of Example 5, indicating that the addition of gallium arsenide powder and manganese oxide to the core rod material does not have a negative impact on the mechanical properties of the composite optical fiber.
[0055] The conventional techniques described in the above embodiments are existing technologies known to those skilled in the art, and therefore will not be described in detail here.
[0056] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.
Claims
1. The use of pyrethroids in enhancing the mechanical and heat resistance properties of the fiber core material of a composite optical fiber for a fluorescence detection system, wherein the composite optical fiber for the fluorescence detection system comprises: The core rod, whose material components include semiconductor selenium powder; The fiber core layer is made of optical fiber core material. The fiber core material includes pyrethroid-modified polymethyl methacrylate; The core rod is prepared by: using a melt casting method, selenium powder is loaded into a quartz tube with a diameter of 3 mm, heated with a flame gun to turn the powder into a liquid, and then cooled to room temperature; then the glass tube is removed by dissolving with hydrofluoric acid to obtain the core rod. The method for preparing the optical fiber core material includes: A certain weight proportions of permethrin, methyl methacrylate, initiator, and n-butyl mercaptan are added to the reaction flask of the prepolymerization device, stirred evenly, and heated to 80-85°C. The prepolymerized core material is poured into the mold cavity of the rod mold, reacted at a constant temperature for 40-48 hours, and then heated to 100°C to continue polymerization for 10-12 hours to obtain modified polymethyl methacrylate rods. To prepare the composite optical fiber, a modified polymethyl methacrylate rod is taken and polished according to the required size. Then, a cylindrical hole is machined inside the rod, and a core rod of appropriate size is selected and filled into the modified polymethyl methacrylate rod to obtain a composite preform. Next, it is vacuum solidified at 170~180℃ for 1~1.5h and then drawn on a standard Rasta to obtain the composite optical fiber. The raw material components of the optical fiber core layer material include, by weight, 85-96 parts of methyl methacrylate, 4-10 parts of pyrethroid, 0-5 parts of N-tert-butyl-1,1-dimethyl-1-(2,3,4,5-tetramethyl-2,4-cyclopentadien-1-yl)silaneamine, 0.1-2 parts of initiator, and 0.05-3 parts of n-butylthiol.
2. The use according to claim 1, characterized in that: In the fabrication process of the composite optical fiber, the fiber drawing temperature is 290~320℃.
3. The use according to claim 1, characterized in that: In the fiber drawing process of the composite optical fiber preparation steps, the metal electrode material is continuously fed into the preform through pulleys, and then drawn together to form a composite optical fiber.
Citation Information
Patent Citations
Method of preparing photosensitivity multipolymer doped with optical-fibre preformed bar and the fiber core material
CN101041270A
Plastic optical fiber prefabricated rod, preparation method and application thereof
CN102120350A
Manufacturing method for multi-core optical fiber preform
CN107601838A
Plastic optical fiber core layer material and preparation method and application thereof
CN108794679A
Method for preparing semiconductor microsphere particles based on fluid instability in optical fiber
CN110228790A